Computational fluid dynamics of bladder voiding using 3D dynamic MRI - Shahid, Labib; Gonzalez‐Pereira, Juan Pablo; Johnson, Cody; Bushman, Wade; Roldán‐Alzate, Alejandro (International journal for numerical methods in biomedical engineering, 2024)
Over the last couple of decades, image‐based computational fluid dynamics (CFD) has revolutionized cardiovascular research by uncovering hidden features of wall strain, impact of vortices, and its use in treatment planning, as examples, that were simply not evident in the gold‐standard catheterization studies done previously. In the work presented here, we have applied magnetic resonance imaging (MRI)‐based CFD to study bladder voiding and to demonstrate the feasibility and potential of this approach. We used 3D dynamic MRI to image the bladder and urethra during voiding. A surface mesh processing tool was developed to process the bladder wall prior to executing a wall‐motion driven CFD simulation of the bladder and urethra. The obtained flow rate and pressure were used to calculate urodynamic nomograms, which are currently used in the clinical setting to assess bladder voiding dysfunction. These nomograms concluded that our healthy volunteer has an unobstructed bladder and normal contractility. We calculated the work done to void the bladder and propose this as an additional quantitative metric to comprehensively assess bladder function. Further, we discuss the areas that would improve this relatively new methodology of image‐based CFD in urodynamics. We present a computational method for characterizing bladder and urethral urine flow during voiding using 3D dynamic MRI and computational fluid dynamics. This method would aid analyzing lower urinary tract symptoms and complement multichannel urodynamic studies by providing comprehensive anatomical and flow dynamics information that were previously unavailable. We computed existing urodynamic nomograms noninvasively and propose new methods to quantify bladder function.